Understanding and Measuring Social Capital : A Multidisciplinary Tool for Practitioners - Grootaert, Christiaan; Van Bastelar, Thierry (Washington, DC: World Bank, 2013)
The importance of social capital for sustainable development, is by now well recognized. Anthropologists, sociologists, political scientists, and economists have in their own ways, demonstrated the critical role of institutions, networks, and their supporting norms and values, for the success of development interventions. This success often hinges on accurate assessments of social capital in target communities. But the nature, and impact of social capital - the institutions, relationships, attitudes, and values that govern interactions among people - are not easily quantified. "Understanding and Measuring Social Capital" provides a conceptual review, and measurement tools, in a form readily available for development practitioners. The book discusses the respective value of quantitative, and qualitative approaches to the analysis of social capital, illustrating the discussion with examples, and case studies from many countries. It also presents the Social Capital Assessment Tool, which combines quantitative, and qualitative instruments to measure social capital at the level of household, community, and organization, drawing on multidisciplinary, empirical experiences, an application which can provide project managers with valuable baseline, and monitoring information about social capital in its different dimensions.